PRINSIP WASATIYYAH DALAM TAFSIR MUHAMMAD ‘ALI AS-SABUNI: Konsep Moderasi dan Perdamaian dalam Wacana Keberagamaan - Kustiadi, Umar (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
Muhammad ‘Ali As-Sabuni provides the principles of wasatiyyah represented in the terms of peace which are reformulated through his interpretation. This formulation certainly has a new character in the concept of wasatiyyah initiated by Muhammad ‘Ali As-Sabuni. To deepen the concept, the researcher departed from two problem formulations. based on this search, this research answers two important problems; a) how is the construction of Muhammad ‘Ali As-Sabuni's interpretation of the meaning of wasat, b) what is the conceptual offer of Muhammad ‘Ali As-Sabuni's interpretation of the discourse of religious moderation in the context of peace. The method used in this research is descriptive-analysis with the type of library research (library research). While the type of data analysis method uses critical analysis. The results/findings of this research show three principles of the meaning of wasat, namely: wasatiyyah as a bridge of religious moderation, wasatiyyah in social interaction, and wasatiyyah in interfaith relations. based on the results of the thinking initiated by Muhammad ‘Ali As-Sabuni, it builds an interpretative construction that gives birth to a moderate-humanist discourse in creating religious harmony. This finding certainly opens the discourse of moderation to modern society as well as answering that the meaning of wasat is not only limited to narrow textual assumptions but provides a color of peace built on inter-religious harmony.